2019
DOI: 10.1371/journal.pone.0212060
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of aging on plasma proteins levels in older adults – associations with kidney function and hemoglobin levels

Abstract: Background A targeted proteomics chip has been shown to be useful to discover novel associations of proteins with cardiovascular disease. We investigated how these proteins change with aging, and whether this change is related to a decline in kidney function, or to a change in hemoglobin levels. Material and methods In the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) study, including 1,016 participants from the general population aged 70 at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
(29 reference statements)
3
15
0
Order By: Relevance
“…We have previously shown that the majority of the investigated 84 cardiovascular‐related proteins increased over a 10‐year period . We now extend those observations by identifying eight proteins for which the changes over time were related to changes in both BMI and WHR; of these, the strongest associations were observed for leptin and FABP4.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We have previously shown that the majority of the investigated 84 cardiovascular‐related proteins increased over a 10‐year period . We now extend those observations by identifying eight proteins for which the changes over time were related to changes in both BMI and WHR; of these, the strongest associations were observed for leptin and FABP4.…”
Section: Discussionsupporting
confidence: 71%
“…Using the proximal extension assay (PEA) technique for measurement of multiple proteins on a targeted proteomics assay, we have discovered that a range of proteins is related to several cardiovascular and metabolic traits in the community‐based Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) study . We also recently showed that the majority of 84 cardiovascular candidate proteins increased over time when measured at ages 70, 75, and 80 years in the PIVUS cohort .…”
Section: Introductionmentioning
confidence: 99%
“…Previous cross-sectional studies have shown that the levels of many circulating proteins have an inverse relationship with eGFR [31,32]. A longitudinal study using an Olink proteomics panel (although not one used in our study) found that for 74% of the 84 proteins measured, protein levels rose as eGFR fell [33]. For many proteins, it is unclear whether this inverse relationship with renal function reflects cause or effect.…”
Section: Krt19 Psip1)mentioning
confidence: 51%
“…Inclusion criteria for a manuscript included healthy individuals, proteomics results published on or after 2010, publications/authors provided list of significant/all proteins. Thirty three manuscripts met the inclusion criteria, including 12 that covered human plasma (Enroth et al, 2015; Lehallier et al, 2019; Lind et al, 2019; Menni et al, 2015; Ngo et al, 2016; Orwoll et al, 2018; Santos‐Lozano et al, 2020; Sun et al, 2018; Tanaka et al, 2018; Wang, Zhu, et al, 2019; Wang, Zhang, et al, 2019; Ye et al, 2019), 9 from 14 different matrices in humans (Baird et al, 2012; Bakun et al, 2014; Bell‐Temin et al, 2019; Gueugneau et al, 2014; Heinze et al, 2018; Hennrich et al, 2018; Ubaida‐Mohien et al, 2019; Waldera‐Lupa et al, 2014; Wang, Wang, et al, 2018), and 12 publications covering 21 different species/matrices (Amin et al, 2020; Angelidis et al, 2019; Braun et al, 2016; Cutler et al, 2017; Drulis‐Fajdasz et al, 2018; Gebert et al, 2020; Heinze et al, 2018; Kelley et al, 2018; Meng et al, 2020; Stauch et al, 2015; Wang, Zhu, et al, 2019; Yu et al, 2020). The age range of participants included in these studies spanned from 14 to 103 years, and measures were carried out using multiple platforms including but not limited to liquid chromatography–mass spectrometry (LC‐MS)‐based proteomics, multiplexed proteomic assay using modified aptamers (SOMAscan) and Proximity Extension Assay (PEA, O‐Link) (Gold et al, 2010; Lundberg et al, 2011).…”
Section: Methodsmentioning
confidence: 99%